Speaking From Reading Science by Working on Text - Bakhtiyorovna, Sattarova Marjona; Ravshanovna, Sheranova Guzal (Universitas Muhammadiyah Sidoarjo, 2022)
The article analyzes the methodological rules and principles of speech development in primary school reading lessons.